PP-002 Compounding for paediatric patients-increasing quality through mechanisation?. (14th February 2016) - Telsnig, L; Pointinger, A
Abstract : Background: In order to assess the quality of extemporaneously prepared capsules for paediatric patients, we conducted a series of uniformity tests in 2012. Results showed considerable fluctuations in quality of mixing, being recognised as most critical and dependent on personal skills. Purpose: Based on the results of our previous study we chose to test mechanisation using a blender in the preparation of paediatric capsules. The aim of our study was to ensure sufficient mixing capacity of the tested device in real life conditions and consequently to improve the uniformity of content of our capsules. Material and methods: To mimic a realistic setting we compounded manually grinded acetylsalicylic acid and maize starch using Torpac's ProMixer V-Blender. The loading and mixing process was conducted corresponding to the manufacturer's instructions. From each mixture samples were taken at representative points of the blender, quantified by high performance liquid chromatography and analysed according to European Pharmacopoeia 8. Results: Initially, 7 mixtures were analysed, which all complied with pharmacopoeial requirements by meeting the criterion 'uniformity of content of single dose preparations' (2.9.40). Nevertheless, deviations from the expected value were high (up to 41.7%) with an average of 11.3%. Furthermore, 6 mixtures failed the pharmacopoeial test 'uniformity of content' (2.9.6). Troubleshooting revealed an unsatisfactory grinding process and showed the necessity to ensure homogeneous particle size. Addressing this issue by introducing a sieving step, another 5 mixtures were analysed, all of which satisfied both pharmacopoeial directives, with maximum deviations of 24.2% and an average of 5.9%. Conclusion: Our study indicates that the use of a blender significantly improves uniformity of content compared with manually blended capsules, but coherent particle size is needed for optimal results. Further testing with capsules composed of crushed tablets will be carried out before implementation into practice. References and/or Acknowledgements: Raffl M, Pointinger A. Quality in pharmaceutical compounding for paediatric patients. Eur J Hosp Pharm 2012;19:100 No conflict of interest.